2006
DOI: 10.1007/s00125-006-0402-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of family history of diabetes and lifestyle factors on abnormal glucose regulation in middle-aged Swedish men and women

Abstract: Aims/hypothesis We investigated associations between abnormal glucose regulation and family history of diabetes, separately and in combination with lifestyle risk factors. Subjects and methods This cross-sectional study comprised 3,128 men and 4,821 women, aged 35-56 years, half with a family history of diabetes. Oral glucose tolerance testing identified subjects with previously undiagnosed prediabetes (IFG, IGT) and type 2 diabetes. Information on lifestyle factors was obtained by questionnaire. Biological in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
40
5
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 39 publications
15
40
5
5
Order By: Relevance
“…An earlier study from Sweden also found a 50% increased risk of prediabetes in participants with FHD [4]. In our metaanalysis, the OR was lowest for iIGT (1.25) compared with iIFG (1.37) and IFG+IGT (1.64).…”
Section: Discussionsupporting
confidence: 60%
“…An earlier study from Sweden also found a 50% increased risk of prediabetes in participants with FHD [4]. In our metaanalysis, the OR was lowest for iIGT (1.25) compared with iIFG (1.37) and IFG+IGT (1.64).…”
Section: Discussionsupporting
confidence: 60%
“…A positive parental history was not associated with sex, ethnicity, fasting glucose, age, C-reactive protein, interleukin-6, anger, depression, or social support. Similar to previous observations, subjects with a family history of diabetes had a higher BMI (4,5) (27 ± 6.6 vs. 24.5 ± 3.8 kg/m 2 , P = 0.07), significantly higher insulin resistance as derived from homeostatis model assessment (5) (median 1.70 [interquartile range 1.19–1.90] vs. 1.30 [0.80–1.82], P = 0.04), and significantly higher fasting plasma insulin (5) (10.3 ± 9 vs. 6.7 ± 4 μU/ml, P = 0.02). However, the relationships of insulin resistance and fasting plasma insulin to parental history were mediated by BMI but not age, ethnicity, or sex.…”
supporting
confidence: 88%
“…A similar pattern was seen for each group (IFG, IGT, IFG+IGT) when analysed separately. There was no significant change in fasting IGFBP-1 values in the 19 individuals with diabetes diagnosed on the basis of glucose values 2 h after oral glucose (20 μg/l [95% CI [15][16][17][18][19][20][21][22][23][24][25][26][27] and 20 μg/l [95% CI [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] at baseline and follow up, respectively). In those who developed diabetes, fasting IGFBP-1 concentrations were higher at the 10 years followup compared with baseline (paired t tests; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Study population The present study was an incident casecontrol study of Swedish white men who were part of a 10 year follow-up epidemiological survey, the Stockholm Diabetes Prevention Program (SDPP), which is described elsewhere [20][21][22]. The SDPP is a population-based study of individuals aged 35-56 years who were without known diabetes at the time of recruitment in 1992-1994.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation